Clinical knowledge and attitudes of Turkish physicians toward rabies caused by animal bites - (:unkn) unknown (My University, 2011)
Rabies is an endemic infectious disease and one of the most important causes of human mortality in both underdeveloped and developing countries. In Turkey, 167,000 individuals are believed to be victims of animal bites annually. In this study, we investigated Turkish physicians' knowledge and clinical awareness of rabies caused by animal bites. This was a cross-sectional, analytical study. We used questionnaires that collected demographic information and assessed the physicians' basic knowledge of rabies as well as the management of animal bites suspected of causing rabies. The questionnaires were completed in person with physicians who work in Istanbul. A total of 890 physicians responded to our cross-sectional questionnaires. The maximum possible scores for basic and clinical rabies- related knowledge was 100 points each. The average score for basic rabies knowledge was 64.5 ± 16, while the average score for clinical rabies knowledge was 62.8 ± 12. However, 68% of the physicians in the study were not aware of the proper method for cleaning wounds as a first-line treatment in postexposure prophylaxis. In addition, 38.4% of the physicians in the study did not understand the administration of vaccines together with immunoglobulin as part of postexposure prophylaxis. We also found that 79% of the physicians did not know the correct doses of vaccines, while 37.6% did not know the correct sites and routes of vaccine administration. Finally, 30% of the physicians were not aware of the correct vaccine schedules in postexposure prophylaxis. Our data indicate that Turkish physicians' basic and clinical knowledge of rabies was insufficient. Rabies prophylaxis educational programs should be designed to educate physicians on the guidelines provided by the World Health Organization and the Advisory Committee on Immunization Practices for the treatment of rabies caused by animal bites.
Keywords: Adult; Female; Humans; Surveys and Questionnaires; Animals; Turkey; Cross-Sectional Studies; Male; Attitude of Health Personnel; Physicians; Bites and Stings; Professional Competence; Rabies; Rabies Vaccines